2013
DOI: 10.1063/1.4815985
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of (110) anti-phase boundaries in GaP on Si(001)

Abstract: High quality III/V-layers grown on Si enable a variety of optoelectronic devices. The performance of such devices is limited by anti-phase domains forming at monoatomic steps on the Si-surface. To date the atomic structure of anti-phase boundaries, which affects the charge distribution at polar interfaces, is unknown. Here, we use CS-corrected scanning transmission electron microscopy to reveal the atomic structure of the anti-phase boundaries in III/V-semiconductors, choosing GaP as a model system. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…In addition to showing the preferential annihilation of APBs along {112} planes [30], Beyer et al, observed that in similarly grown GaP-on-Si samples APBs oriented along {110} planes displayed a tendency to jump one or more atomic planes, thereby creating a finite thickness to the APB [31]. Thus, increasing growth temperature can increase the jump probability for APB planes and enhance the annihilation rate.…”
Section: Resultsmentioning
confidence: 92%
“…In addition to showing the preferential annihilation of APBs along {112} planes [30], Beyer et al, observed that in similarly grown GaP-on-Si samples APBs oriented along {110} planes displayed a tendency to jump one or more atomic planes, thereby creating a finite thickness to the APB [31]. Thus, increasing growth temperature can increase the jump probability for APB planes and enhance the annihilation rate.…”
Section: Resultsmentioning
confidence: 92%
“…The enhanced diffusivity of Ga and P along and across the GaP/Si interface, results in an equal distribution of Si-Ga and Si-P bonds at the interface. The exact element depth distribution across this interface is the subject of ongoing high-resolution TEM investigations [37], which show an extension of the intermixed layer at the interface of 3-4 atomic layers. In all nucleation layers grown using the FME mode, no stacking faults were detected in either GaP orientation ([1 1 0] or [À 1 1 0]) or in plan view investigations.…”
Section: Annealing Of the Homoepitaxial Si-buffer: Influence Of Si Sumentioning
confidence: 99%
“…This indeterminacy, for instance, is directly relevant to a possible differentiation between antiphase domains of GaP films grown on Si(001). 17 The improved orientation determination method presented in this letter is sensitive to the breaking of inversion symmetry in GaP. This characteristic symmetry breaking is visible most prominently by the opposite stacking sequence of Ga and P layers along [111] and ½ 1 1 1 as displayed in the left part of Fig.…”
mentioning
confidence: 91%
“…The implications of the broken inversion symmetry in these materials are seen, for example, in microstructural effects like antiphase domains and polarity inversion which need to be controlled in growth processes. [14][15][16][17] In this respect, EBSD is an attractive option for nondestructive analysis of semiconductor thin film systems, because of its typical depth sensitivity in the order of a few tens of nanometers. 18 In this letter, we demonstrate absolute orientation mapping for polycrystalline GaP, overcoming a fundamental limitation of the standard kinematic EBSD orientation determination which is used up to now.…”
mentioning
confidence: 99%